Acute Myeloid Leukaemia with Vitreous Haemorrhage: Management Challenge in a Third World Country. (28th October 2020) - Olatinwo, A T; Ogbenna, A A; Bolarinwa, A
Abstract: Casestudy: Leukaemic ophthalmopathy is commoner in acute myeloid leukaemias. Ophthalmic involvement in leukaemias is classified into: Primary or Secondary. Methods: A 35-year-old man with history of working in an oil and gas company for 3years who presented 9months ago on account of one month history of recurrent fever, occasional bone pain and generalised body weakness.Had associated history of passage of dark coloured urine, mouth ulcers, mouth bleeds and dizziness. CBC at presentation showed WBC of 102, 300/mcl with 79% blasts, hemoglobin of 5.4g/dL, platelet count of 12, 000/mcl. Symptoms were consistent with leukostasis, and he had leukoreduction with exchange blood transfusion and hydroxyurea. Bone marrow aspirate confirmed the diagnosis of AML FAB M2. Bone marrow biopsy showed hypercellular marrow with increased myeloid series, other series depressed. Three days after admission, he complained of painless blurred vision bilaterally and feeling of objects appearing reddish, a review by ophthalmologist with an assessment of bilateral retinal haemorrhage secondary to AML. B – Scan done showed whitish elevated hyperechoic mass (parapapillary) with moderate dot echoes in the vitreous bilaterally. They planned for dilated fundoscopy and advised haematologist to commence chemotherapy as planned. He then had standard induction with cytarabine and daunorubicin.Post chemotherapy showed pancytopenia secondary to chemotherapy. Further review by Ophthalmologist showed bilateral vitreous haemorrhage secondary to bilateral choroidal mass and then planned for vitrectomy and also had bilateral intravitreal bevacizumab Day 14 bone marrow exam showed hypocellularity with absence of blasts indicating remission. He subsequently underwent cycle 1 of consolidation with high-dose cytarabine with the goal to proceed with allogeneic hematopoietic stem cell transplant (HSCT). Post consolidation, patient has had surgeries of both eyes and subsequently regained full vision in both eyes. Though patient is yet to re-present for post consolidation chemotherapy despite adequate counsel due to financial constraints and yet to have allogeneic hematopoietic stem cell transplant (HSCT) and last showed up for follow up four months ago. Results: Patient regained full vision in both eyes Conclusion: This case illustrates that vitreous haemorrhage in Patients with AML can be effectively managed in a resource limited setting.